A systematic review: the appraisal of the effects of metformin on lipoprotein modification and function - K. G. Kheniser; S. R. Kashyap; T. Kasumov (Wiley, 2019)
Summary Aims Metformin is a commonly prescribed anti‐hyperglycaemic pharmacological agent, and it remains a staple in the management of type II diabetes. In addition to metformin's glucose lowering effects, research has indicated that metformin inhibits glycation‐mediated and oxidative modification of lipoprotein residues. The purpose was to discuss the effects of metformin as it relates to high‐density lipoprotein (HDL) and low‐density lipoprotein (LDL) modification. Materials and methods The purpose was to conduct a narrative and pragmatic review on the effects of metformin as it pertains to HDL and LDL modification. Results High‐density lipoprotein (HDL) concentration is a quantitative measure and therefore does not provide insight into its function, which is a qualitative property. Dysfunctional HDLs are unable to carry out functions normally associated with HDL because they can be modified by glycating agents. Metformin may counteract HDL dysfunction by abating HDL modification. Reductions in HDL modification may improve reverse cholesterol transport ability and thus possibly diminish cardiovascular risk. Similarly, metformin‐mediated attenuations in LDL modification may reduce their atherogenic potency. Conclusion Metformin may partially ameliorate HDL dysfunction and reduce LDL modification by inhibiting alpha‐dicarbonyl‐mediated modification of apolipoprotein residues; consequently, the results are salient because cardiovascular disease incidence may be reduced given that reverse cholesterol transport activity predicts risk, and modified LDL are proatherogenic.